Folie en Christ à la romaine et à la moscovite : deux exemples de la religiosité chrétienne au XIXe siècle - Irina Mironenko Marenkova (Conserveries Mémorielles)
Lifes of two Christian saints, a French pilgrim Benoît-Joseph Labre and a Russian fool for Christ Ivan Semenovitch Grigoriev, had numerous similar traits. However very different social position and politics of the Catholic and Orthodox Churches induced very different destiny of the two cults. Labre was canonized in 1881 and his figure was used in catholic propaganda to diffuse religious values, Grigoriev, admired by common people, has never obtained official recognition.